IMPLEMENTASI PEMBELAJARAN BERBASIS PROYEK UNTUK MENINGKATKAN MINAT BELAJAR SISWA PADA MATA PEMBELAJARAN MATEMATIKA DI KELAS V SD - Omri Mareyuda Purba; Syahrial; Akhmad Faisal Hidayat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Mathematics learning is a systematically designed process to enable students to achieve understanding and mastery of the mathematical concepts being taught. However, in practice, many students show low interest in learning mathematics, which affects their comprehension and engagement in the learning process. This study aims to describe the implementation of project-based learning and how it improves students' learning interest in mathematics for Grade V students at SDN 134/I Merbau. This research is a classroom action research (CAR), carried out in two cycles, where each cycle consists of two meetings and includes four stages: planning, implementation, observation, and reflection. The subjects of this study were 13 fifth-grade students of SDN 134/I Merbau, consisting of 5 boys and 8 girls. The data collection techniques used were observation, questionnaires, and documentation. The observation instruments used were a student interest questionnaire and an observation sheet for the learning implementation activities. The results of the study showed that the implementation of the project-based learning model could increase students' interest in learning mathematics. The researcher measured the level of student interest using a questionnaire instrument, which showed a success rate of 59.48% in the first cycle and 90.89% in the second cycle. Based on the results, it can be concluded that the implementation of project-based learning can improve students' learning interest, as evidenced by the increase exceeding 70%.